Factors Influencing Intention to Adopt Internet Technology among Rural Homestay Operators in Malaysia - Osman, Zahir; Zulaika Zakaria, (Journal of Technology Management and Business, 2020)
Abstract: The purpose of this study is to develop a direct effect understanding of perceived usefulness, perceived ease of use, trust, and attitude on homestay operators’ intention to adopt internet technology in their homestay business in Malaysia. The Structural Equation Model (SEM) was used to analyse the casual relationships between independent variables and dependent variables. The model was developed and later tested by adopting the Partial Least Square (PLS) procedure on data collected from a survey that yielded 307 usable questionnaires. The findings showed that perceived usefulness, perceived ease of use and trust have a significant and positive influence on homestay operators’ attitude. Attitude, then found to positively and significantly influence the homestay operators’ intention to adopt internet technology in their homestay business. The findings imply that the relationship amongst perceived usefulness, perceived ease of use, trust, and attitude on homestay operators’ intention to adopt internet technology will lead to the increase of their homestay guests. This study uses Smartpls 3.0 and SPSS 18.0 to test the hypothesis and analyse respondents’ profile, respectively.